Direct Torque Control of VSI Fed Induction Motor with Fuzzy Controller - N. Sai Krishna, G. Narasimha Reddy (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The Direct Torque Control (DTC) methods for AC machines are commonly utilized in many variable speed drives, especially in case the torque control is more desired than speed control. Two major problems that are usually related with DTC drives are: 1) switching frequency that varies with operating conditions and 2) high torque ripple. To solve these problems and at the same time intermit the simple control structure of DTC, a constant switching frequency torque controller is proposed to replace the conventional hysteresis-based controller. The major advantages of the Voltage Source Inverter (VSI) are combines with those of the DTC technique, producing the appropriate voltage vectors under 0.9 input power factor operations. The results prove the high quality and robustness in the system dynamic response and minimize in the both steady-state and transient motor ripple torque. The proposed switching scheme for VSI based DTC of IM drive select the necessary switching vectors for control of torque with small variations of the stator flux within the hysteresis band. This paper presents a novel control scheme based on Fuzzy Logic Controller (FLC). This paper reviews the research and development in direct torque control of VSI fed IM.Such a review helps the highly effective control strategies for AC machine to provide a very fast torque and flux control. In this technical context an overview of VSI fed induction motor has been carried out based on the reports from the literature present in past two recent decades.